THE PURSUIT OF AVIATION SECURITY AND SAFETY: DALIL NAQLI AND DALIL AQLI - Sena, Afen; Baby Callista, Annisa; Nina Rizkyanti, Fadhilla (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2024)
Aviation security and safety are crucial aspects of the aviation industry that require serious attention from various parties. Along with technological developments and increasing air traffic, the challenges in maintaining aviation security and safety are increasingly complex. This research aims to examine the role of naqli and aqli postulates in improving aviation security and safety. The research methodology used a qualitative approach with a case study method, involving in-depth interviews with aviation experts, religious experts, and aviation regulators, as well as analysis of policy documents and official reports using data collection literature study and interview. The results showed that the principles of dalil naqli, such as justice and social responsibility, significantly shape aviation safety policies. Meanwhile, the dalil aqli approach, based on rationality and modern technology, effectively reduces accident risk and improves operational efficiency. This study concludes that integrating naqli and aqli arguments can create a more comprehensive aviation safety policy that various parties accept.